Stress levels and coping strategies of selected parents of children with autism - Amonoy, Mary Justine Clarise Alfonso
The increasing incidence of autism in the Philippines as of 2009 has undeniably resulted to more parents experiencing stress. This reality inspired the researcher to undertake this study to: identify the stress levels of parents and children with autism (CWA); determine if there is a difference in these stress levels as compared using the following factors, gender of parent, educational attainment, monthly family income, number of children, age of CWA, number of CWA caregivers and time spent by parents with the CWA; classify their effective strategies based on their demographic characteristics and generate a list of coping strategies that CWA parents could use. The survey questionnaires were given to 30 CWA parents, chosen through convenience sampling, to collect data on demographic characteristics and stress levels. Ten CWA parents participated in the interview to identify their stress-coping strategies. Both quantitative and qualitative analyses were applied. The stress level were compared using Analysis of Variance and t-Test. The frequencies of the coping strategies of CWA parents were also determined. Results show that there are no significant differences between the stress levels among these parents as compared using the demographic factors. Seven coping aspects were found: emotional, educational, physical, social, spiritual, financial, and familial. Acceptance of the situation, education in autism, diversion of attention to other activities, joining support groups, prayers, financial management, and open communication within the family were used CWA parents to cope with their stress.